The Extrovert and Introvert Students’ in Speaking Ability of English Department at IAIN Langsa - Selvianita Rahayu (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2020)
This research investigates about Extrovert and Introvert students in speaking ability of English Department at IAIN Langsa. Extrovert personality has characteristic interest in the external object and more friendly. Introvert are people that hold all of from external happenings, and dislike of large social. The aim of study investigated about whether significant difference between Extrovert and introvert students in speaking ability. The research method of study used qualitative method with descriptive research. The subject of research consisted 10 students who are 3 extrovert students and 7 introvert students. the instrument that used in this research was observation and interview. Based on the result of research students with extrovert type more active, friendly, and responsively in speaking class. Based on the observation and interview result students’ extrovert they more enjoyed in speaking class and brave to give comments or speak in class meeting. They were type personality who are preferring to practice speaking and share their opinions more often. While, students of their introverted personality are more silent, they only speak as necessary. The introvert students do not more to express themselves and they were afraid to share their opinions. It can be concluded that students extrovert personality more active in speaking ability and their interest in speaking class.